2020
DOI: 10.1038/s41598-020-74477-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of uterine rupture in Ethiopia: a systematic review and meta-analysis

Abstract: Uterine rupture is a serious public health concern that causes high maternal and perinatal morbidity and mortality in the developing world. Few of the studies conducted in Ethiopia show a high discrepancy in the prevalence of uterine rupture, which ranges between 1.6 and 16.7%. There also lacks a national study on this issue in Ethiopia. This systematic and meta-analysis, therefore, was conducted to assess the prevalence and determinants of uterine rupture in Ethiopia. We followed the Preferred Reporting Items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
(100 reference statements)
1
8
0
3
Order By: Relevance
“…The prevalence found in the present study is similar to that of African countries (18.8%) [14]. In Latin America and the Caribbean, the pregnancy rate is the second highest in the world, second only to the one found in the Sub-Saharan Africa [13].…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence found in the present study is similar to that of African countries (18.8%) [14]. In Latin America and the Caribbean, the pregnancy rate is the second highest in the world, second only to the one found in the Sub-Saharan Africa [13].…”
Section: Discussionsupporting
confidence: 83%
“…This could be explained by optimal ANC's role in the identification of potential risk exposure to uterine rupture and bolster for immediate and planned intervention such as cesarean section(C/S) ( 102 ). Home delivery, obstructed labour, prolonged labour, severe anemia, previous history of C/S, and partograph utilization were identified as risk factors for uterine rupture in Ethiopia ( 103 105 ). All those risk factors are handled during ANC visits by providing iron folate, encouraging institutional delivery, and planning selective C/S ( 106 , 107 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, osseous dystocia accounted for 10.9% of uterine rupture cases. 2,7,12,20,23 Fetal dystocia type of fetal macrosomia (21.2%) and dystocicpresentation (15.3%) were also found. The use of uterotonics through oxytocin infusion (16.5%), whether or not preceded by cervical ripening with misoprostol (2.4%).…”
Section: Scarred Uterusmentioning
confidence: 92%
“…12 In two meta-analysis conducted by Alemu et al (OR 3.23 95% CI 2.12-4.92) and Desta et al (OR 9.95 95% CI 3.09-32.0) relating respectively to 12 and 16 different studies, the history of cesarean section was confirmed as a risk factor for uterine rupture. 2,20 This risk increases with a short birth interval. 2,21,22 Other circumstances…”
Section: Scarred Uterusmentioning
confidence: 99%